Recent plastic technologies development of basal texture control to improve the property of wrought Mg alloys-a review - Xiaoyu Feng; Lifei Wang; Xiang Chen; Kunkun Deng; Xiao Wang; Liuwei Zheng; Hongxia Wang; Qiang Zhang; Ho Kwon; Bin Xing; Kwang Seon Shin (Journal of Materials Research and Technology)
The room temperature plasticity of magnesium alloy is poor because of its unique crystal structure. After extrusion or rolling process, the grain orientation of as-cast Mg alloy tends to be the same, and it shows obvious intense basal texture, which makes it show obvious tensile and compressive asymmetry and anisotropy. Texture control plays a crucial role in enhancing their mechanical properties, formability, and corrosion resistance. The grain c-axis of the extruded Mg alloy is deflected at a certain angle through predeformation treatment, shear deformation and other composite severe plastic deformation (SPD) processes. This results in refined grain size and adjusted texture orientation. The process also facilitates recrystallization, and the orientation of newly formed grains during continuous dynamic recrystallization (CDRX) is similar to that of the parent crystals but may deviate slightly. The discontinuous dynamic recrystallization (DDRX) process produces new grains with a randomly distributed orientation. Consequently, the initial dense basal texture has been decreased, the basal slip systems are significantly activated, and plasticity is greatly improved. The continued action of non-basal slip concurrently enhances plasticity.The present paper provides a comprehensive overview of the texture regulation technology and mechanism of Mg alloy subjected to shear strain and torsional deformation, including extrusion, rolling, and bending. The beneficial effects of texture control on the mechanical characteristics, formability, and corrosion resistance of Mg alloys were elucidated by integrating twinning, recrystallization, and non-basal slip processes. The future development trends and challenges of Mg alloy plastic technology are finally proposed.